Advanced Techniques for Efficient Modeling of Electrically Large Structures on Desktop PCs - Kolundzija, Branko M.; Tasic, Miodrag S.; Olcan, Dragan I.; Zoric, Dusan P.; Stevanetic, Srdjan M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The method of moments (MoM), applied to surface integral equations (SIEs) in the frequency domain, enables very accurate analysis of composite metallic and dielectric structures. Particularly, on a desktop PC, the electrical size of solvable problems is very limited by memory and time resources. This limit can be significantly extended by using advanced techniques, which are shortly revealed. The focus of the paper is to present results that illustrate current possibilities of MoM/SIEs solution on a desktop PC: (1) monostatic RCS of a cube of side 80 ?, (2) beam steering of an array of 30 by 30 microstrip patch antennas at 9.2 GHz, and (3) beam steering of 4 by 4 patch antennas at 5 GHz, placed on a 19 m long helicopter.